A systematic review and meta-analysis on how different dexamethasone administration regimes impact total joint arthroplasty outcomes - Wang, Can; Luo, Chenjing; Tang, Xiaoxue; Luo, Li; Zeng, Yuerong; Zhang, Yumei; Wang, Xuan (Frontiers in Pharmacology, 2025)
BackgroundPostoperative pain following total joint arthroplasty is a critical factor influencing patient recovery. This meta-analysis evaluated the efficacy and safety of single-dose, repeated-dose, and split-dose perioperative dexamethasone regimens for managing postoperative pain in patients undergoing total joint arthroplasty.MethodsRandomized controlled studies (RCTs) comparing repeated or split-dexamethasone to single intravenous dexamethasone in patients having total knee/hip arthroplasty were retrieved from Pubmed, the Cochrane Library, Web of Science and Embase databases from inception to October 2024. Using RevMan 5.2, a meta-analysis was performed to evaluate primary outcomes including pain scores, length of stay, and incidence of postoperative rescue analgesia, as well as secondary outcomes such as the incidence of adverse events. Heterogeneity was assessed via I2 statistics, and study bias was evaluated using the Cochrane Risk of Bias Assessment Tool.ResultsTwelve trials were included. The results showed that repeated-dose dexamethasone did not differ from single-dose dexamethasone in rest or movement pain scores at 24 h, but significantly reduced both rest (mean difference [MD] = −0.45, 95% confidence interval [CI]: -0.62 to −0.29, P < 0.00001, I2 = 41%) and movement (MD = −0.69, CI: −0.83 to −0.55, P < 0.00001, I2 = 36%) pain scores at 48 h. They also had shorter stays (MD = −0.28, 95% CI: -0.47 to −0.09, P = 0.004, I2 = 71%), lower rates of needing postoperative rescue analgesia (relative risk [RR] = 0.26, 95% CI: 0.11 to 0.63, P = 0.003, I2 = 72%) and postoperative nausea and vomiting [PONV] (RR = 0.47, 95% CI: 0.24 to 0.95, P = 0.04, I2 = 60%). Moreover, patients receiving a single dose of dexamethasone had lower movement scores 24 h postoperatively (MD = 0.26, 95% CI: 0.03 to 0.48, P = 0.02, I2 = 61%) compared to patients with a split-dose of dexamethasone. No significant differences in adverse event rates were observed between single-dose and split-dose dexamethasone.ConclusionCompared to patients receiving a single-dose or split-dose of dexamethasone, the administration of repeated doses of dexamethasone can mitigate postoperative pain, reduce the requirement for supplementary opioids, shorten the duration of hospitalization, and decrease the incidence of PONV following arthroplasty.Systematic Review Registrationhttps://inplasy.com/inplasy-2023-10-0023/.